2015
DOI: 10.3402/meo.v20.26615
|View full text |Cite
|
Sign up to set email alerts
|

Elective courses for medical students during the preclinical curriculum: a systematic review and evaluation

Abstract: ObjectivePreclinical medical student electives are prevalent at medical schools across the United States, but the range of electives available and their impact on medical student education are not well described in the literature. The objective of this article is to review the literature relating to preclinical medical student electives and their impact on medical student educational outcomes.MethodsWe reviewed studies that met the following criteria: English-language articles describing preclinical US-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 44 publications
3
62
0
Order By: Relevance
“…From our own survey of information about optional/elective courses available on the internet, we agree with Agarwal et al () that there is a paucity of available information that is useful to evaluate pedagogic efficacy. We have particularly observed that many, if not most, medical schools in the USA have embraced the concept.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…From our own survey of information about optional/elective courses available on the internet, we agree with Agarwal et al () that there is a paucity of available information that is useful to evaluate pedagogic efficacy. We have particularly observed that many, if not most, medical schools in the USA have embraced the concept.…”
supporting
confidence: 79%
“…Agarwal et al () have recently provided a systematic evaluation of ‘preclinical’ elective courses in the medical curriculum and have reported that “the range of electives available and their impact upon medical student education are not well described in the literature.” It is recognized that the prime purpose of such courses is to introduce flexibility in the medical course and to allow the students to following their own individual pathways by pursuing their own personal interests. In addition, Agarwal et al () stated that electives “teach medical students useful skills, increase student wellness” (although no evidence was provided to support this) and “impact eventual career choices” (again no evidence was made available for this assertion). Of course, anatomists have developed gross anatomy electives (sometimes with dissection) for ‘political’ reasons in order to counter the loss of gross anatomy or practical training within the ‘core’ courses.…”
mentioning
confidence: 99%
“…Numerous institutions have demonstrated the feasibility of using a community health fair for interprofessional education (Agarwal et al, 2015;Bridges, Davidson, Odegard, Maki, & Tomkowiak, 2011;Haber et al, 2014;Hope et al, 2005;Odegard et al, 2009. However, studies demonstrating the effectiveness of a health fair for increasing students' interprofessional skills are limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One method that has been widely employed for providing students with an opportunity for an interprofessional educational experience is the implementation of an interprofessional health fair (Agarwal, Wong, Sarfaty, Devaiah, & Hirsch, 2015;Bridges, Abel, Carlson, & Tomkowiak, 2010;Diwan, Perdue, Lee, & Grossman, 2015;Haber, Spielman, Wolff, & Shelley, 2014;Hope et al, 2005;Kolomer, Quinn, & Steele, 2010;Odegard et al, 2009;Towle, Godolphin & Kline, 2015). However, as the IPE experience concept has evolved, comparisons of different experiences have proven difficult, typically due to the broad range of outcomes approaches used, diversity in models, and somewhat limited descriptions of learning objectives (Davidson, Smith, Dodd, Smith, & O'Loughlan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is common practice in other countries for electives to form part of their medical degree programmes (1)(2)(3). For example, in 1993, Great Britain saw the nationwide introduction of electives as a mandatory component in all medical degree programmes (4).…”
mentioning
confidence: 99%